Do d(GCGAAGC) Cations Retain the Hairpin Structure in the Gas Phase? A Cyclic Ion Mobility Mass Spectrometry and Density Functional Theory Computational Study - Wan, Jiahao; Nytka, Marianna; Qian, Haocheng; Lemr, Karel; Tureček, František (Journal of the American Society for Mass Spectrometry, 2023)
d(GCGAAGC) is the smallest oligonucleotide with a well-defined hairpin structure in solution. We report a study of multiply protonated d(GCGAAGC) and its sequence-scrambled isomers, d(CGAAGCG), d(GCGAACG), and d(CGGAAGC), that were produced by electrospray ionization with the goal of investigating their gas-phase structures and dissociations. Cyclic ion mobility measurements revealed that dications of d(GCGAAGC) as well as the scrambled-sequence ions were mixtures of protomers and/or conformers that had collision cross sections (CCS) within a 439-481 Å2 range. Multiple ion conformers were obtained by electrospray under native conditions as well as from aqueous methanol. Arrival time distribution profiles were characteristic of individual isomeric heptanucleotides. Extensive Born-Oppenheimer molecular dynamics (BOMD) and density functional theory (DFT) calculations of d(GCGAAGC)2+ isomers indicated that hairpin structures were high-energy isomers of more compact distorted conformers. Protonation caused a break up of the C2···G6 pair that was associated with the formation of strong hydrogen bonds in zwitterionic phosphate anion-nucleobase cation motifs that predominated in low energy ions. Multiple components were also obtained for d(GCGAAGC)3+ trications under native and denaturing electrospray conditions. The calculated trication structures showed disruption of the G···C pairs in low energy zwitterions. A hairpin trication was calculated to be a high energy isomer. d(GCGAAGC)4+ tetracations were produced and separated by c-IMS as two major isomers. All low energy d(GCGAAGC)4+ ions obtained by DFT geometry optimizations were zwitterions in which all five purine bases were protonated, and the ion charge was balanced by a phosphate anion. Tetracations of the scrambled sequences were each formed as one dominant isomer. The CCS calculated with the MobCal-MPI method were found to closely match experimental values. Collision-induced dissociation (CID) spectra of multiply charged heptanucleotides showed nucleobase loss and backbone cleavages occurring chiefly at the terminal nucleosides. Electron-transfer-CID tandem mass spectra were used to investigate dissociations of different charge and spin states of charge-reduced heptanucleotide cation radicals.